Effect of optimised cutting constraints by AlCrN/epoxy coated components on surface roughness in CNC milling. (27th June 2019) - Bejaxhin, A. Bovas Herbert; Paulraj, G.
Here in this work, the milling slots are produced on EN32 MS plate machined with coated HSS end milling cutters and fusion bonded epoxy coated BT40 tool holders. Tool coatings TiN, TiAlN, and AlCrN are preferred in the process of PVD method. This experiment benefited to differentiate the surface roughness for various speed, feed, and depth of cut. The prediction of effective stress for tool work interaction through the dynamic simulator deform 3D. An L27 array is designed with a controllable response to machining conditions, coating types which affect the desired output Ra. Taguchi and ANOVA approach supports to determine the most significant parameters. The influence of coated tools pooled with fusion-bond epoxy (FBE) coated taper end BT40 milling tool holder used to elevate Ra. Thus the optimised values of surface roughness were obtained and the effect of input parameters was identified on specimen roughness. Comparisons have made in between the roughness and stress effective of simulator tool for inspiring the clear solution.